A DIFFERENTIATED APPROACH IN A SEMINAR SESSION ON SALTYKOV-SHCHEDRIN'S NOVEL THE GOLOVLYOV FAMILY - Yakhshimuradova G. A (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the methodology of conducting a seminar session on M. E. Saltykov-Shchedrin's novel The Golovlyov Family (1875–1880) within a university course on nineteenth-century Russian literature, applying a differentiated approach. The article proposes a concrete structure for the session, a system of questions and tasks at three levels of complexity, and techniques for sustaining a unified academic discussion in a mixed-ability student group.